Hermeneutika Emillio Betti dan Aplikasinya dalam Menafsirkan Sistem Kewarisan 2:1 pada Surat an-Nisa Ayat 11 - Labib Fahmi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2018)
One characteristic of the inheritance system in Islamic law that distinguishes it from other inheritance systems is that there are differences in division between the male and female parts, as stated in the Koran in Surat an-nisa verse 11, namely the male part is equal to two part of women, this rule seems to have been standardized in the study of various fiqh in various schools of thought that are mu'tabaroh. Even the system has been standardized and recognized legally in the Religious Courts throughout Indonesia through the legalization of the Compilation of Islamic Law in Indonesia which is required to be used throughout the Religious Courts in the country. Not only legal and recognized in the Religious Courts, but also several cases of dispute resolution outside the court also hold fast to the text of the verse 11 paragraph in resolving inheritance disputes committed by several legal experts’/community leaders outside the court. This paper shows a interpretation from the another perspective with hermeneutic of Emmilio Betti. She was a philosopher, theologian and legal expert from Italy, a figure of hermeneutics apad 19 who adheres to the principle of verstehen as a form of understanding that can be traced and justified methodologically that is objective interpretation that can be used as the basis of science, for Betti, meaning should be derived from the text and not included in the text. Using Hermeneutics Betti in interpreting this verse will produce a verstehen, that the meaning of verse 11 of the epistle must also be related to the cause of revelation in solving this inheritance problem comprehensively and objectively, regardless of this verse can be used as a textual context or the context of the verse want a settlement of inheritance according to revelation, and the Prophet has proven that the verse can fulfill the justice of the friends who ask about the distribution of inheritance among friends.